Psychosocial and Physiological Determinants of Continued Exclusive Breastfeeding at 6 Months’ Corrected Age in Late Preterm Infants - Jinxiu Chen; Qinghua Li; Honghui Wen; Qiuxia Liang; Weiqiang Zhang; Xiujuan Liao; Yanqing Tang (Breastfeeding Medicine, 2026)
Background and Objective: Exclusive breastfeeding (EBF) is essential for neonatal survival and long-term development; however, late preterm infants (34 +0 –36 +6 weeks of gestation) consistently exhibit lower breastfeeding persistence than term infants. Breastfeeding sustainability in this population is influenced by both psychosocial conditions and physiological readiness. This study aimed to identify modifiable psychosocial and physiological determinants—including prenatal breastfeeding intention, family caregiving support, skin-to-skin contact, workplace breastfeeding support, and the timing of the early secretory activation—associated with continued EBF at 6 months among late preterm infants. Methods: This retrospective cohort study reviewed late preterm infants admitted to a tertiary perinatal center between January 2020 and December 2022. Demographic, perinatal, and feeding-related variables were extracted from electronic medical records using the REDCap platform. Key exposures included prenatal breastfeeding intention, postnatal caregiving modality, daily duration of skin-to-skin contact, workplace breastfeeding support, and early secretory activation timing. The primary outcome was EBF duration, assessed at corrected ages of 6, 12, and 24 weeks. Propensity score matching (PSM) (1:1) was performed to balance baseline maternal and neonatal characteristics. Results: After PSM, 124 mother–infant dyads were included in the final analysis. The mean maternal age was 29.7 years, and 54% of mothers reported an intention to breastfeed for more than 6 months. Breastfeeding duration was strongly associated with prenatal intention, with over 80% of mothers who planned continued EBF at 6 months achieving this goal ( p = 0.004). Shared family caregiving was associated with significantly longer breastfeeding duration compared with exclusive maternal care (odds ratio [OR] = 3.144, p = 0.001). Longer daily skin-to-skin contact demonstrated a dose–response relationship with breastfeeding persistence (OR = 3.038, p < 0.001). Workplace breastfeeding support was independently associated with prolonged EBF, particularly among mothers with established prenatal intention (OR = 2.142, 95% confidence interval [CI]: 1.105–4.334, p = 0.007). Additionally, an earlier secretory activation (≤2 days postpartum) was a strong predictor of continued EBF at 6 months, independent of maternal intention (OR = 3.227, 95% CI: 1.014–5.610, p = 0.001). Conclusion: Both psychosocial support and physiological factors play critical roles in sustaining breastfeeding among late preterm infants. Prenatal breastfeeding intention, family caregiving support, skin-to-skin contact, workplace breastfeeding accommodations, and early secretory activation independently and jointly contribute to continued EBF at 6 months duration. Targeted interventions addressing these modifiable factors may improve breastfeeding sustainability in this high-risk population.